Fast redox switches lead to rapid transformation of goethite in humid tropical soils: A Mössbauer spectroscopy study - Bhattacharyya, Amrita; Kukkadapu, Ravi K.; Bowden, Mark; Pett‐Ridge, Jennifer; Nico, Peter S. (Soil Science Society of America journal, 2022)
Humid tropical forest soils experience frequent rainfall, which limits oxygen diffusion and creates redox heterogeneity in upland soils. In this study we gauged the effect of short‐term anoxic conditions on Fe mineralogy of relatively Fe‐ and C‐rich surface soils (C/Fe mole ratio ∼5) from a humid tropical forest in Puerto Rico. Soils subjected to 4‐d oxic/anoxic oscillation were characterized by selective chemical extractions, Mössbauer spectroscopy (MBS), and X‐ray diffraction. Chemical extraction data suggested that rapidly switching redox conditions had subtle effects on bulk Fe mineralogy. Mössbauer, on the other hand, indicated that (a) the soil Fe is a mixture of goethites of varying characteristics with minor contributions from ferrihydrite (<5%) and Fe(III)‐organic matter (OM) phases (∼10%), and (b) anoxic conditions rapidly transformed all forms of goethite to relatively stable Fe oxides. Such fast changes in goethite features could be due to rapid depletion and sorption of bio‐released structural Al or sorbed OM onto residual soil components. The rapid temporal changes in MBS parameters and corresponding pore water nominal oxidation state of C values suggest that Fe‐C transformations in these upland tropical soils are complex and intricately coupled. A comprehensive understanding of the fate of Fe, Al, and OM (Fe‐organic moieties) during redox switches and concurrent changes in pore water chemistry is critical for development of robust transport models in humid tropical soils, which are subject to episodic low‐redox events. Core Ideas Iron oxide crystallinity increases during rapid reduction events in humid tropical soils. Depletion of Al and redistribution of organic C on Fe‐oxide surfaces lead to increased crystallinity of goethites. Mossbauer spectroscopy at 225 K is critical to identify molecular scale changes in mineralogy.